How successful people Lead - Maxwell, John (United State of America : Center Street, 2013)
Following the format of Maxwell's previous successful derivatives "How Successful People Think" (almost 300,000 sold) and "Make Today Count" (over 150,000 sold), this pocket-sized abridgement of "The 5 Levels of Leadership" will reveal how successful leaders grow.
Keywords: Leadership. Leadership; Social aspects